IC 6610 Method And Cost Of Quarrying Limestone At The Plant Of The Calaveras Cement Co., San Andreas, Calif. - Introduction - Robert H. Townsend (The National Institute for Occupational Safety and Health (NIOSH), 1933)
The following paper discusses the mining, transportation, and crushing methods, with costs, at the San Andreas plant of the Calaveras Cement Co. It is one of a series, prepared for and published by the U. S. Bureau of Mine describing methods used in cement-rock quarries throughout the country. These papers are designed to disseminate technical information regarding the methods used. The cost tabulations represent operating expenditures only and not total cost. It is recognized that publication of total costs mightin some instances cause embarrassment to individual producers as well as to the industry as a hole. On the other hand, operating costs are essential to the technical discussion and study of the methods employed. The attention of the reader is specifically called to this differentiation in order that no misunderstanding of the scope of the cost-tabulations shall ensue.